2007
DOI: 10.1007/978-3-540-74466-5_88
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Preference Systems in P2P Networks

Abstract: The original publication is available at www.springerlink.comInternational audienceIn this work we study preference systems suitable for the Peer-to-Peer paradigm. Most of them fall in one of the three following categories: global, symmetric and complementary. All these systems share an acyclicity property. As a consequence, they admit a stable (or Pareto efficient) configuration, where no participant can collaborate with better partners than their current ones. We analyze the representation of such preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…b -matching theory and its variants have already applications in a variety of real-world situations, including dating agencies, college admissions, roommates attributions, assignment of graduating medical students to their first hospital appointment, or kidney exchanges programs [11,14,15,24,25]. Regarding decentralized networks, b -matching already gave a theoretical proof for upload/download correlations in incentive networks like BitTorrent [10] and highlighted small-world phenomena in latencybased networks [8].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…b -matching theory and its variants have already applications in a variety of real-world situations, including dating agencies, college admissions, roommates attributions, assignment of graduating medical students to their first hospital appointment, or kidney exchanges programs [11,14,15,24,25]. Regarding decentralized networks, b -matching already gave a theoretical proof for upload/download correlations in incentive networks like BitTorrent [10] and highlighted small-world phenomena in latencybased networks [8].…”
Section: Introductionmentioning
confidence: 97%
“… Gai et al showed that symmetric marks can define all possible acyclic preferences, including global preferences[8]. Therefore it is natural to consider how close to global preferences a symmetric matrix is.…”
mentioning
confidence: 99%
“…Stability as an underlying concept is also used to allocate graduating medical students to hospitals in many countries [8]. sr on the other hand has applications in the area of P2P networks [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dealing with this market by using the DA-CDM model enables 133 assigning flights to slots through a one-to-one relationship that 134 respects the preferences of each allocation and is always guaran-135 teed to provide a stable result (Vossen & Ball, 2006 (Ergin & Sonmez, 2006;Gai et al, 2007;Roth et al, 2004). 244 As the use of runways of an airport can be considered as a 245 limited resource of aeronautical and airport infrastructure, the 246 matching markets models can be associated to ATFM processes 247 considering the demand and capacity of runways for aircraft.…”
mentioning
confidence: 96%
“…76 This model, based on Matching Markets Mechanisms of the Game 77 Theory, allows to include the preferences of the Airport 78 Management, next to those of the ATC agents and the airlines. 79 The choice of Game Theory for our solution is due to the fact 80 that such approaches enable the incorporation of the preferences 81 of different stakeholders (Sonmez & Unver, 2011) and have been 82 successfully implemented in labor markets (Roth & Sotomayor,83 1989), school admission process (Ergin & Sonmez, 2006), P2P 84 networks (Gai et al, 2007), and organ donation markets (Roth, 85 Sonmez, & Unver, 2004), and generally in domains that involve (Balakrishnan, 2007;Pinheiro, Vinicius, Weigang, Melo, & Alba, 88 2007; Weigang, Alves, & Omar, 1997. Intelligent systems 89 for the reallocation of flights, gate scheduling, and related prob-90 lems (Chan, Chow, So, & Chan, 2012;Cheng, Ho, & Kwan, 2012;91 Genc, Erol, Eksin, Berber, & Guleryuz, 2012;Jo, Jung, & Yang, 92 1997; Kuwata & Oohama, 1997) anteed that airlines report their cancellations due to the lack of 124 incentive to do so (Schummer & Rakesh, 2013).…”
mentioning
confidence: 99%